Implementation of Gamification-Based Learning Method in PAI Learning to Increase Student Learning Motivation in SMAN 1 Tahunan - Rohman, Risky Zainur; Darnoto, Darnoto (Mauriduna : Journal of Islamic Studies, 2026)
Islamic Religious Education (IRE) requires instructional innovation that not only emphasizes conceptual understanding but also fosters character development and the application of religious values in daily life. The limitations of conventional lecture-based methods, which often result in monotonous learning activities, highlight the need for more engaging approaches aligned with technological advancements. This study aimed to examine the effectiveness of gamification-based learning in increasing student participation, strengthening students' understanding of repentance (taubat), trust in God (tawakal), fear of Allah (khauf), and hope in His mercy (raja'), and creating a more dynamic learning environment at SMA Negeri 1 Tahunan, Jepara. The study employed a qualitative approach with a case study design, with participants selected through purposive sampling. Data were collected through observations, interviews, and documentation, and analyzed qualitatively using data reduction, data display, and conclusion drawing. The findings indicate that the implementation of gamification-based learning through the use of the Quizizz platform enhanced students' learning enthusiasm, collaboration, and active engagement in Islamic Religious Education, supported by adequate school facilities and the active role of teachers, although time limitations and variations in students' abilities remained challenges.